Asma e doenças alérgicas em escolares de população ribeirinha da região leste da Amazônia - Freitas, Marly Sarmanho de Souza [UNIFESP] (2011)
Background: epidemiological studies have focused on possible association between helminth infection and the development of asthma and/or allergies. Objectives: to evaluate the association between helminth infection and asthma and its relation to serum levels of total and specific IgE for A. lumbricoides and aeroallergens, besides evaluating possible relation between BCG scar and allergic sensitization. Methods: cross sectional study in 400 schoolchildren from two Amazon Islands. A standardized written questionnaire (asthma module) from International Study of Asthma, Allergies in Childhood protocol was administered and asthmatic children were those with current wheezing. The following procedures were done: skin prick test (positive test with papule mean diameter > 3mm); blood samples for assessment of serum levels of total and specific IgE for A. lumbricoides and aeroallergens (positive those with levels > 0.36 kU/L); feces samples for helminths examination (positive = infected with at least one helminth); mean diameter of BCG vaccine scar measurement. Analyses were assessed for both islands together and non-parametric tests were applied obtaining 5% of significance level. Results: there was no significant difference between infected and non-infected children with helminths related to asthma expression, save for having physician-diagnosed asthma that was more frequent in helminths infected children. Serum levels of total and specific IgE for A. lumbricoides were higher in infected children. Significant correlations between serum levels of total and specific IgE for aeroallergens to Periplaneta americana and Ascaris lumbricoides among those infected and among those non-infected was for B. germanica e B. tropicalis. Significant correlation between papule mean diameter and serum level of specific IgE for D. pteronyssinus e B. tropicalis among those not infected. Mean diameter of BCG vaccine wasn´t different among children with asthma and those without, as well as there was no correlation between serum levels of total and specific IgE. Conclusions: parasite infections are not associated with either asthma expression or to allergic sensitization, but positive association was verified between physician-diagnosed asthma and helminth infection. More studies are necessary to clarify helminth infection role on asthma and allergic diseases.